Improving the components of health-saving technologies in a modern university - I. A. Kabanova; V. P. Chicherin; N. V. Terekhova; E. R. Tokareva (Вестник университета)
Nowadays, one of the important missions of higher educational institutions is the organisation and introducing students to a culture of health. The purpose of this study is to propose a strategy for the development of health-saving technologies by implementation of project activities into the educational process based on the Physical Education Department at the State University of Management for the formation of competencies in the chosen professional activity. The sociological survey was carried out among students at the State University of Management. The questionnaires included questions on students’ attitudes towards physical culture as an integral component of a healthy lifestyle. The degree of interest of the respondents in project activities in general and on the basis of the Department of Physical Education at the university, in particular, to improve the acquired professional competences was determined. The results of the study point to the need to modernise approaches to the formation of healthy lifestyle values, including the organisation of physical culture events, the development of a marketing plan to attract mass attention to the sports life of the university, where the main role is given to self-education and the realisation of the individual’s potential through active participation in university sporting life.